Cacat Las Pada Pembuatan Frame Pintu Air dengan Menggunakan Gas Metalarc Welding (GMAW) di PT. Barata Indonesia (Persero) Divisi Sumber Daya Air - Adhen Mahessa Putra,; Hadi Wibowo, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the types of welding defects that occur in the manufacturing process of floodgate frames using the Gas Metal Arc Welding (GMAW) method at PT. Barata Indonesia (Persero) Air Resources Division. The research method was conducted through direct observation during internships, visual documentation, and interviews with welding technicians and operators. The analysis focused on common defects such as porosity, pin holes, overlapping, and inconsistent weld appearance. The results indicate that the main causes of defects are material cleanliness, inappropriate welding parameter settings, and inconsistent welding techniques. Improvements were made through re-welding, parameter adjustments, and improving work surface cleanliness. This study demonstrates the importance of quality control in the welding process to increase structural strength and soundness. These results are significant as technical input for the company in improving production quality and provide practical learning for students in applying welding engineering knowledge in the industrial world.